SAMPLE FIELD TRIP - Spickard, Jim (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The focus of today’s field trip is "religious stories." You are, of course, to note the demographics, physical setting, events, and messages (as described in McGuire’s "protocol"). Through these, however, you are to look for the stories people tell one another, and the ways in which they interpret these stories to give meaning to their lives. You may find these stories in hymns, prayers, Bible readings, or in the sermon; you may also find them in the rituals you see acted out. A typical service will contain one (or perhaps two) such stories. Note the stories told and the meanings people draw from them.